2017
DOI: 10.1111/cen.13329
|View full text |Cite
|
Sign up to set email alerts
|

Preconception TSH and pregnancy outcomes: a population‐based cohort study in 184 611 women

Abstract: Preconception TSH elevation was associated with increased risk of adverse pregnancy outcomes, even within the normal nonpregnant range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 34 publications
4
40
1
2
Order By: Relevance
“…It has been documented in several studies that high-normal TSH is associated with some adverse effects concerning reproduction and with certain abnormalities in metabolic processes. Concerning the former, either preconception (e.g., Chen et al [8]) or first trimester high-normal TSH (e.g., Hernandez et al, Kianpour et al. [9,10]) are associated with both infertility and unfavorable pregnancy outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…It has been documented in several studies that high-normal TSH is associated with some adverse effects concerning reproduction and with certain abnormalities in metabolic processes. Concerning the former, either preconception (e.g., Chen et al [8]) or first trimester high-normal TSH (e.g., Hernandez et al, Kianpour et al. [9,10]) are associated with both infertility and unfavorable pregnancy outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…An example of good practice in this regard is China's national free preconception health examination project which offers access to preconception health examinations including thyroid hormone measurement in rural parts of China ( 14 ). A recent analysis of 184,611 pregnant participants in this programme showed an association between higher preconception TSH concentrations and risks of miscarriages and pre-term loss, highlighting opportunities for modifying pregnancy outcomes with preconception care ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…For each of these outcomes, more studies failed to show a significant association with SCH than demonstrating a positive association 9. However, the largest cohort to date published in 2017 showed that women with a single TSH prepregnancy of 4.29–10mU/L (n=7140) had an increased risk of adverse pregnancy outcomes (odds ratio [OR] 1.15, 95% CI 1.10 to 1.22) including spontaneous abortion (OR 1.50, 95% CI 1.32 to 1.70), fetal death (OR 1.58, 95% CI 1.10 to 2.28) and preterm birth (OR 1.20, 95% CI 1.08 to 1.34), even with adjustment for age, body mass index, smoking, thyroid disease and obstetric history 10. Interestingly, an increased risk of adverse events (OR 1.06, 95% CI 1.03 to 1.08) was also shown for women with TSH levels of 2.50–4.28mU/L (n=44 239).…”
Section: Does Sch During Pregnancy Cause Harm?mentioning
confidence: 99%